Salt intake and salt‐reduction strategies in South Asia: From evidence to action - Kamal Ghimire; Shiva Raj Mishra; Gautam Satheesh; Dinesh Neupane; Abhishek Sharma; Rajmohan Panda; Per Kallestrup; Craig S. McLachlan (2021)
The World Health Organization recommends salt reduction as a cost-effective intervention to prevent noncommunicable diseases. Salt-reduction interventions are best tailored to the local context, taking into consideration the varying baseline salt-intake levels, population's knowledge, attitude, and behaviors. Fundamental to reduction programs is the source of dietary salt-intake. In South Asian countries, there is a paucity of such baseline evidence around factors that contribute to community salt intake. Upon reviewing the electronic literature databases and government websites through March 31, 2021, we summarized dietary salt intake levels and aimed to identify major sources of sodium in the diet. Information on the current salt reduction strategies in eight South Asian countries were summarized, namely Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka. One hundred twelve publications (out of identified 640) met our inclusion-exclusion criteria for full text review. Twenty-one studies were included in the review. Quality of the included studies was assessed using the US National Heart, Lung, and Blood Institute assessment tool. The primary result revealed that mean salt intake of South Asian countries was approximately twice (10 g/day) compared to WHO recommended intake (< 5 g/day). The significant proportion of salt intake is derived from salt additions during cooking and/or discretionary use at table. In most South Asian countries, there is limited data on population sodium intake based on 24-h urinary methods and sources of dietary salt in diet. While salt reduction initiatives have been proposed in these countries, they are yet to be fully implemented and evaluated. Proven salt reduction strategies in high-income countries could possibly be replicated in South Asian countries; however, further community-health promotion studies are necessary to test the effectiveness and scalability of those strategies in the local context.